1994
DOI: 10.1159/000147661
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Arbor Alterations in the Medial Superior Olivary Neurons of Neonatally Underfed Rats

Abstract: Golgi-Cox-stained bipolar cells of the medial superior olive (MSO) were analyzed in control and undernourished Wistar strain rats at 12, 20, 30 and 40 days of age. Undernutrition significantly reduced the number of dendrites and the extension of ipsilateral dendritic prolongations, with no effects upon the cross-sectional somal area and minimal alterations in the corresponding contralateral dendritic branches. The data suggest that in underfed rate, afferents from the receptors projecting to the MSO via the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The finding of neuronal MTB and LSO dendritic arbor alterations associated with neonatal undernutrition and ear binaural occlusion provided new information on the plastic cytoarchitectonic reorganization of the first synaptic relays of the auditory system. Regarding this, the present data agree with the results of other studies showing that visual and somatosensory cues deprivation decreases, while polysensorial stimulation increases the dendritic arborizations of neurons in motor pyramids [39], visual cortex [40,41], claustrum [42], amygdala [8], hippocampus [43], and medial superior olivary neurons [33]. Moreover, there is a sharp increase in the number of spines or dendritic branching after renutrition or ear and eye opening.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The finding of neuronal MTB and LSO dendritic arbor alterations associated with neonatal undernutrition and ear binaural occlusion provided new information on the plastic cytoarchitectonic reorganization of the first synaptic relays of the auditory system. Regarding this, the present data agree with the results of other studies showing that visual and somatosensory cues deprivation decreases, while polysensorial stimulation increases the dendritic arborizations of neurons in motor pyramids [39], visual cortex [40,41], claustrum [42], amygdala [8], hippocampus [43], and medial superior olivary neurons [33]. Moreover, there is a sharp increase in the number of spines or dendritic branching after renutrition or ear and eye opening.…”
Section: Discussionsupporting
confidence: 93%
“…4, 5) may first be explained by the prolonged time of sound transmission in bone provoked by the binaural ear occlusion with the rubber glue that promotes the neuronal LSO dendritic arbor maturation and its modulatory projection on the inner hair cells of the organ of Corti [31][32][33]. This fact correlates well with the late MTB neuronal maturation primarily associated with the air-sound transmission when the auditory channel is opened [31].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the past, a number of studies have shown that perinatal undernutrition in the rat delays the maturation of sensory systems and causes the expression of altered motor patterns; these effects lead to a significant deficiency of somatosensory, auditory, visual, and chemosensory stimulation that may be essential for long-term behavioral performance [1][2][3][4][5][6][7][8]. Perinatal undernutrition mainly interferes with the anatomical organization of central nervous system (CNS) areas which undergo a phase of postnatal cell proliferation; these areas include the cerebral and cerebellar cortices, the hippocampus, central amygdaloid nucleus, olfactory bulb, and solitary tract nucleus, and they participate in the head movements, mouth opening and closing, chewing, food ingestion, and chemosensory CNS integration [8,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%